DICTATORIAL GOVERNMENT AND MAPUCHE PEOPLE FROM 1973 UNTIL 1978. RECONFIGURATION OF THE CHILEAN COLONIALISM - Caniuqueo Huircapán, Sergio (Revista de Historia Social y de las Mentalidades, 2024)
This article discusses Mapuche people’s diversity, unity and continuity elements within the military dictatorship’s context, between 1973-1978. It is argued that the Mapuche people, constituted by social subjects, generates a response system that allows reassuring itself as a single entity against colonialism. In this way, we are going to present the speech, actions, forms or strategies, from both the military and the Mapuche people for intervening in the political scene during this period, in the IX region. We address facts, which in our view, are relevant to understand antagonisms and unities, and the elements that made possible both identity and continuity as a people.